Application of Cooperative Learning Model Think Pair Share To Improve Writing Skills Free Poetry Elementary School Grade V 015 Gunung Bungsu XIII Koto Kampar - Fitri, Ilas Fitri Ilas; Kurniaman, Otang Kurniaman Otang; Noviana, Eddy Noviana Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research is still low skills writing free verse Elementary School fifth grade students 015 Gunung Bungsu XIII Koto Kampar. The research problems are Is the application of cooperative learning model Think Pair Shareuntuk improve writing skills free verse SDNegeri 015 fifth grade students Gunung Bungsu XIII Koto Kampar?. This study aims to improve the skills of writing free verse Elementary School fifth grade students 015 Gunung Bungsu XIII Koto Kampar with the application of cooperative learning model Think Pair Share. This study is a Class Action Research (CAR). The subjects were students of class V Elementary School 015 Gunung Bungsu XIII Koto Kampar, amounting to 28 people. Data collection instruments in this thesis is the teacher and student activity sheets and write free verse. The results reveal that the free poetry writing skills derived from the value of the daily tests before treatment with an average of 45.84 increase in the first cycle with the average being 64.58 and increased in the second cycle increased by an average of 83.03. The activities of teachers in the learning process at the first meeting siklusI 66.66 % and the second meeting increased to 75 %. Cycle II first meeting and the second meeting of 86.11 % increase to 97.22 % The results of the data analysis of student activity on the first cycle of the first meeting with an average of 63.88 % and a second meeting increased to 72.22%. Cycle II first meeting and the second meeting of 83.33 % increase to 94.44 %. The results of the study in class V Elementary School 015 Gunung Bungsu XIII Koto Kampar prove that the implementation of cooperative learning model Think Pair Share can improve writing skills free verse Elementary School fifth grade students 015 Gunung Bungsu XIII Koto Kampar.Keywords: Think Pair Share, Free Poetry Writing Skills